'Clases de español': Education and testimonio in the Poetry of Alicia Partnoy. Issue 6 (June 2016) - Dunn, Kate
Abstract : Alicia Partnoy is a survivor of kidnapping, unlawful detention and torture during the 1976–1983 dictatorship in Argentina. She has testified about her experiences at the United Nations, Amnesty International and CONADEP (the Argentine National Commission on the Disappearance of Persons), and continues to campaign against human rights violations. In a close reading of 'Clases de español' from the collection Volando bajito (2005), I will analyse Partnoy's creation of the poet–teacher and how this figure is used to comment on the transmission and educational function of testimonio. The classroom forms an atypical testimonial space, used to reflect on the situation of the exile as well as the responsibilities of those who listen to testimony. This article will examine the possibilities that poetry offers for the expression of testimonio and how Partnoy uses the poetic form to challenge the limitations of linguistic communication.